RELATIONSHIP BALANCED NUTRITION KNOWLEDGE AND PHYSICAL ACTIVITY WITH NUTRITIONAL STATUS THROUGH BODY MASS INDEX (BMI) METHOD IN ADOLESCENTS AT MTSN 1 TRENGGALEK - Nabila Permatasari Widodo; Atik Sri Wulandari; Harsono Wiradinata (Prosiding Seminar Nasional COSMIC Kedokteran, 2024)
Nutrition is a contribution to the health and development of a person. Good nutrition can build a strong immune system, prevent disease and improve health. However, there are still quite a lot of nutritional problems in Indonesia, especially among adolescents in Indonesia. UNICEF data for 2021 states that around a quarter of adolescents aged 13-18 years in Indonesia are stunted, 9% of adolescents are thin or have a low body mass index, while another 16% of adolescents are overweight and obese. This problem of nutrition can be solved one way by knowing what factors can affect a person's nutritional status. The purpose of this study was to analyze the relationship between knowledge about balanced nutrition and physical activity with nutritional status through the body mass index method. The research is observational with a cross sectional research design. The research population consisted of 200 students at MTsN 1 Trenggalek, Trenggalek Regency, with a sample of 117 respondents, which was determined using a systematic random sampling method. The variables consist of the level of knowledge of balanced nutrition and physical activity as independent variables while the dependent variable is nutritional status with the body mass index as the measurement medium. The results showed that there was a relationship between knowledge of balanced nutrition and nutritional status through the body mass index method (p=0.009), and there was a relationship between physical activity and nutritional status through the body mass index method (p=0.021). From the results of data analysis it can be concluded that knowledge of balanced nutrition and physical activity has an effect on nutritional status through the method of measuring Body Mass Index (BMI) in teenage students at MTsN 1 Trenggalek.